2004
DOI: 10.1123/apaq.21.2.139
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity Levels of Students with Mental Retardation and Students Without Disabilities

Abstract: This study compared physical education and recess physical activity levels of elementary school age students with mild mental retardation (MR) and students without disabilities who possessed either high or low cardiorespiratory fitness. For this study, the System for Observing Fitness Instructional Time (SOFIT), a measure of physical activity, was validated for students with mild MR. A significant difference for moderate to vigorous physical activity was obtained between settings. Findings suggest that student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(35 citation statements)
references
References 32 publications
(37 reference statements)
1
33
0
1
Order By: Relevance
“…Other studies of young people and adults with ID have consistently shown negative differences in general fitness and specifically, cardiovascular endurance, muscular strength, endurance, and range of motion (Hartman, Smith, Westendorp, & Visscher, 2014;Salaun, & Berthouze-Aranda, 2012;Cuesta-Vargas, Paz-Lourido, & Rodriguez, 2011;Zhang, Piwowar, & Reilly, 2009;Faison-Hodge & Porretta, 2004). This has been related to general levels of physical activity being lower in this population, however when considering the potential to attain high standards of physical fitness a more mixed picture emerges.…”
Section: Physiological and Fitness Factorsmentioning
confidence: 99%
“…Other studies of young people and adults with ID have consistently shown negative differences in general fitness and specifically, cardiovascular endurance, muscular strength, endurance, and range of motion (Hartman, Smith, Westendorp, & Visscher, 2014;Salaun, & Berthouze-Aranda, 2012;Cuesta-Vargas, Paz-Lourido, & Rodriguez, 2011;Zhang, Piwowar, & Reilly, 2009;Faison-Hodge & Porretta, 2004). This has been related to general levels of physical activity being lower in this population, however when considering the potential to attain high standards of physical fitness a more mixed picture emerges.…”
Section: Physiological and Fitness Factorsmentioning
confidence: 99%
“…Researchers have consistently called for additional studies on inclusion that investigate physical activity opportunities using more diverse samples in a variety of settings (Faison-Hodge & Porretta, 2004;Trost, Pate, Freedson, Sallis, & Taylor, 2001). Furthermore, researchers have recommended that studies are needed investigating the impact of inclusion upon various dimensions of student well-being, such as social determinants of behavior and effects of inclusion upon all students (Block & Malloy, 1998;Houston-Wilson et al, 1997;Obrusnikova et al, 2003;Place & Hodge, 2001).…”
Section: Inclusive Physical Educationmentioning
confidence: 99%
“…Faison-Hodge and Porretta (2004) compared physical education and recess physical activity levels of elementary school children with mild mental retardation (MR) and students without disabilities who had low or high cardiorespiratory fi tness. They found students with MR and those with low fi tness had similar physical activity patterns in physical education and recess settings.…”
Section: Inclusive and Noninclusive Environmentsmentioning
confidence: 99%
“…Among the direct observational tools available, the System for Observing Fitness Instruction Time (McKenzie, Sallis, & Nader, 1991) and the Children's Activity Rating Scale (Puhl, Greaves, Hoyt, & Baranowski, 1990) have been used for measuring the physical activity levels of children with various disabilities, including intellectual disabilities, developmental disabilities, and hearing impairments (e.g., Faison-Hodge & Porretta, 2004;Taylor & Yun, 2007). Both tools measure students' physical activity levels either live or from videotapes using time-sampling methods.…”
Section: Assessing Physical Activity Levels Of Students With Disabilimentioning
confidence: 99%